Is CBDC evolutionary or revolutionary? What economic history can teach us - Pierre L. Siklos (Centre for International Governance Innovation (CIGI), 2023)
Looking at six historical examples, this paper explores the relationship between technology and monetary arrangements in the context of central bank digital currency (CBDC). The Industrial Revolution in the United Kingdom, the greenbacks era in the United States and the end of private money in Canada are among the examples that illustrate the role of the private sector in the development of money, the role of governments in overseeing key functions of money and the impact of economic crises. The author sees CBDC as an evolution, not a revolution, of the monetary system that can co-exist with traditional currency by performing the same core functions of notes and coins.
Keywords: 330